Media discourse and coalition dynamics: Playing safe is the new trend in media coalition - Raihan, Sheila Anindya Tsany; Prianti, Desi Dwi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This study investigates the cautious approach adopted by media coalitions in framing the discourse surrounding the alteration of the age limit policy for vice presidential candidates in Indonesia in 2024. Using the Discourse Coalition Framework (DCF) and Discourse Network Analysis (DNA), the research explores how media outlets form coalitions through nuanced discourse strategies. This study aims to analyze how online media in Indonesia builds narratives related to changes in the policy of the age limit for vice presidential candidates in the 2024 election. The analysis finds that MediaIndonesia.com and Tempo.co take a non-oppositional stance, crafting narratives that are intentionally cautious and open to multiple interpretations to avoid direct challenges to the MK's decision. This careful positioning often involves complex language that can obscure understanding for the general public, limiting non-experts’ grasp of the legal context. Viva.co.id, however, diverges by presenting clearer narrative patterns that align with specific political coalitions, focusing on justifications and perceived benefits. The study highlights that dominant discourses are often driven by influential figures such as academics, legal experts, and politicians, who serve as primary sources and reinforce the coalition’s influence over public opinion. The application of DNA provides insights into how these actors and their discourses shape public understanding and frame the urgency and legitimacy of the policy. This study underscores that in modern media coalitions, a strategy of "playing safe" is becoming a prevalent approach to managing public perception and discourse on politically sensitive issues.